EMOCIONES Y DEMOCRACIA: ACERCA DE LA COMPASIÓN Y LA IRA EN NUSSBAUM Y GIANNINI. - López Merino, María José (Revista de Filosofía (00348236), 2021)
In the public deliberation of a democracy, what's place have emotions? Especially the emotions of compassion and rage? Is the general question that guides this research. To respond to it, we will focus on the thought of two thinkers who, although they belong to different cultural and academic spaces, have some points of contact in their philosophical perspectives: Martha Nussbaum and Humberto Giannini. Taking charge of the affective turn (Ahmed, 2014) we are looking for investigate the impact on an incomplete democracy they have the passions of compassions and rage have. Especially in the path of democratic transformation, towards more participatory and inclusive ways. Thus, at first, we will dedicate ourselves to describing forms of compassion and forms of rage that benefit democratic deliberation and those that hinder it.